Quality of life in liver transplant recipients and the influence of sociodemographic factors - Maria Isis Freire de Aguiar; Violante Augusta Batista Braga; José Huygens Parente Garcia; Clébia Azevedo de Lima; Paulo César de Almeida; Angela Maria Alves e Souza; Isaura Letícia Tavares Palmeira Rolim (SciELO, 2016)
Abstract OBJECTIVE To verify the influence of sociodemographic factors on the quality of life of patients after liver transplant. METHOD Cross-sectional study with 150 patients who underwent liver transplant at a referral center. A sociodemographic instrument and the Liver Disease Quality of Life questionnaire were applied. The analysis of variance (ANOVA) was performed, as well as multiple comparisons by the Tukey test and Games-Howell tests when p <0.05. RESULTS Old age had influence on domains of symptoms of liver disease (p = 0.049), sleep (p = 0.023) and sexual function (p = 0.03). Men showed better significant mean values than women for the loneliness dimension (p = 0.037). Patients with higher educational level had higher values for the domain of stigma of liver disease (p = 0.014). There was interference of income in the domains of quality of social interaction (p = 0.033) and stigma of the disease (p = 0.046). CONCLUSION In half of the quality of life domains, there was influence of some sociodemographic variable.